+0

# what is the answer to:

0
53
3

log7 + log (n-2) = log 6n

Guest Feb 28, 2017
Sort:

#1
0

Solve for n:
log(7) + log(n - 2) = log(6 n)

Subtract log(6 n) from both sides:
log(7) + log(n - 2) - log(6 n) = 0

log(7) + log(n - 2) - log(6 n) = log(7) + log(n - 2) + log(1/(6 n)) = log((7 (n - 2))/(6 n)):
log((7 (n - 2))/(6 n)) = 0

Cancel logarithms by taking exp of both sides:
(7 (n - 2))/(6 n) = 1

Multiply both sides by 6 n:
7 (n - 2) = 6 n

Expand out terms of the left hand side:
7 n - 14 = 6 n

Subtract 6 n - 14 from both sides:

Guest Feb 28, 2017
#2
+75299
0

log7 + log (n-2) = log (6n)      by a log property we can write

log [7 ( n - 2) ]  = log (6n)       the log bases are the same, so we can solve this

7(n - 2)   =   6n

7n - 14   = 6n          add 14 to both sides, subtract 6n from both sides

n  = 14

CPhill  Feb 28, 2017
#3
0

log7+log(n-2)=log6n             it is true that loga+logb=log(ab)

log(7(n-2))=log6n                   logx is one to one

7(n-2)=6n

7n-14=6n

n=14

Guest Feb 28, 2017

### 8 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details